Microaggressions Faced by International Students in the US with a Discussion on Critical Race Theory - Rodriguez, Miguel; Mohamed, Mirna; Barthelemy, Ramon (Journal of International Students, 2023)
International students make up an increasingly large portion of the US student population, especially among graduate students studying the science, technology, engineering and math (STEM) fields. In this article we analyzed the microaggression experiences of 22 international students in graduate STEM programs at predominantly white institutions. International students, often people of color (PoC), may be subject to facing discrimination within their universities. Our results break down the different types of microaggressions that our participants reported experiencing from faculty, peers and students, both on and off campus. These experiences include individuals insulting a participant’s country of origin, doubting their academic ability, threatening them, and otherwise discriminating against them. Each event reported by our participants is classified into a type of microaggression and is further discussed using Critical Race Theory to connect how international students’ racialized and intersectional experiences are connected to the larger societal issues of racism in the US.